Solubility of Dilute Sulfur Dioxide in Aqueous Poly-Ethylene Glycol 1000 Solutions at 298.15 K and 123.15 kPa - He, Zhiqiang; Liu, Jinrong; Zhang, Na (Asian Journal of Chemistry, 2013)
In present work, solubility data were measured for dilute sulfur dioxide in various aqueous poly-ethylene glycol 1000 (PEG) solutions at 298.15 K and 123.15 kPa and SO2 partial pressures in the range of (0-120) Pa. Measurements were carried out by a saturation method using a glass absorption apparatus, which were controlled at constant temperature by a thermostatic circulation bath with a Beckmann thermometer. Both the gas phase was recirculated in the glass absorption apparatus by an airpump to obtain a series of solubility data. The measurement showed that the solubility of SO2 in the aqueous poly-ethylene glycol 1000 solutions (PEGWs) system increased with the increasing PEG concentration in the whole range of mass fraction.